Perceptions of Faculty Members and Graduate Students on Guidelines in the Face of Use of Text Generative Artificial Intelligence - Torres, Rai G.; Linhalis, Flavia (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics); 2024: Anais da 1ª Conferência Latino-Americana de Ética em Inteligência Artificial, 2024)
Major scientific institutions worldwide have integrated ethics into their policies to promote sound scientific writing practices and to guide authors in the AI era. This article summarizes initial discussions on academic writing and presents a comparison of perspectives on the development of guidelines for scholars across four distinct academic disciplines in higher education. Additionally, we underscore the importance of understanding the perceptions of these academic participants, as this insight can support decision-making by academic leaders. Furthermore, this understanding is essential for reassessing technology literacy within the academic community, with the goal of preserving academic integrity.